Allergic contact dermatitis caused by wound closure tape in a pediatric patient. Issue 3 (24th January 2020) - Tam, Idy; Yu, JiaDe
Abstract: Wound care products are emerging as causes of allergic contact dermatitis (ACD). There are increasing reports of ACD to certain medical adhesives; however, there are no published reports of contact sensitization solely due to wound closure tape such as Steri‐Strips™. Herein, we present the first confirmed case of ACD in a child caused by wound closure tape.